Gratitude, Hope and Humour: Their role in Happiness of Young Adults - Shikha; Sandeep Singh; Taruna (International Journal of Indian Psychȯlogy, 2022)
Every individual desires to be happy in life. Besides external situations the inner strengths of a person are found to play a key role in making life constantly happy and fulfilling. In the present study the strengths of gratitude, hope and humour have been studied to find out their role in happiness amongst college students of age group 18-24 years. These strengths have been measured by the Value in Action Inventory of Strengths (Peterson & Seligman, 2004). The three happiness orientations i.e., meaning, pleasure and engagement have been measured with the help of Orientation to Happiness Scale (Peterson, Park & Seligman, 2005). The data have been analysed by correlation and multiple regression analysis. All the three strengths were found to have significant positive correlation (ranging from 0.22 to 0.45) with each of the happiness orientations. The regression model indicated that gratitude, hope and humour significantly predicted each of the three happiness orientations. Individually, gratitude predicted pleasure and engagement, hope predicted meaning and engagement and humor predicted only pleasure orientation.